Investigating discrepancies in program quality related to youth volleyball athletes` needs support - Bean, C.; Forneris, T.; Brunet, J. (Psychology of Sport and Exercise, 2016)
Abstract: Program quality has been outlined as an important predictor of positive outcomes in youth development programs; however, little evidence exists to support this, particularly within sport. Objective: The purpose of this study was to examine the associations between researcher- and coach-assessed program quality scores as they relate to youth volleyball athletes` basic needs support. Design: Observational data and self-report data were gathered from coaches and youth. Researchers completed 84 observations using a measure of program quality across 14 teams. Coaches completed the same measure at the end of the season and 138 athletes (Mage=14.50) from the 14 teams completed a self-report questionnaire pertaining to needs support. Data were analyzed using polynomial regressions with response surface methodology. Results: Athletes` needs support was significantly (p<0.001) associated with all domains of researcher- and coach-assessed program quality (i.e., safe environment, supportive environment, interaction, engagement), and between 20 and 35% of the variance in athletes` needs support was explained by these variables. The degree of discrepancy between researcher- and coach-assessed program quality increased when progressing through three domains of program quality (safe environment, supportive environment, engagement). Response surface methods indicated that as the degree of agreement increased between researchers` and coaches` ratings of the safety of the environment, supportiveness of the environment, and opportunities for engagement, so did athletes` basic needs support scores in a linear fashion. Conclusions: Practical implications surrounding coach education and the importance of knowledge translation between academics and practitioners are noted, and future research directions are discussed.